2016
DOI: 10.1093/humrep/dew108
|View full text |Cite
|
Sign up to set email alerts
|

Personality in women with endometriosis: temperament and character dimensions and pelvic pain

Abstract: Not applicable to this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 44 publications
1
39
0
1
Order By: Relevance
“…Our findings suggest that personality (anxiety and pessimism vs. positive orientation towards life) may affect this process. A study by Facchin et al (2016) showed that a tendency to experience anxiety and pessimistic worries (i.e., Harm Avoidance) was associated with more severe chronic pelvic pain due to endometriosis. More studies are needed to investigate whether individual characteristics (personality, self-efficacy, self-esteem, coping strategies) may moderate the psychological impact of endometriosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings suggest that personality (anxiety and pessimism vs. positive orientation towards life) may affect this process. A study by Facchin et al (2016) showed that a tendency to experience anxiety and pessimistic worries (i.e., Harm Avoidance) was associated with more severe chronic pelvic pain due to endometriosis. More studies are needed to investigate whether individual characteristics (personality, self-efficacy, self-esteem, coping strategies) may moderate the psychological impact of endometriosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies examined the psychosocial impact of endometriosis without addressing any specific research question focused on individual differences, which seem to play an important role among women with this disease (Facchin et al 2016). For example, no studies have systematically investigated how and why endometriosis differently affects women, such that not all of them are distressed.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is no research systematically exploring the effectiveness of psychotherapy (either cognitive behavioral or psychodynamic therapy) in women with endometriosis. Overall, based on our clinical practice and previous research,7,110,111 we suggest that women may benefit from supportive–expressive psychotherapeutic interventions (either individual or group interventions) aimed at facilitating the expression of deepest thoughts and feelings about endometriosis, as well as at empowering their female identity. Adequately designed trials are needed to define the magnitude of the benefit of psychotherapeutic interventions in different clinical conditions.…”
Section: Psychological Interventionsmentioning
confidence: 71%
“…There is evidence that chronic pelvic pain negatively affects mental health, but recent qualitative research109 has shown that endometriosis might have a negative pervasive impact on women’s psychological health for reasons other than pelvic pain. For instance, the disruption caused by the disease and the inability to restore a sense of biographical continuity is an important source of anxiety and depression 110. This growing body of knowledge, which also suggests the extent to which women’s sense of female identity can be negatively affected by endometriosis, indicates that psychological interventions with distressed endometriosis patients should not be exclusively focused on pain symptoms; a proper psychotherapeutic intervention aimed at helping women integrate endometriosis into their own history should be encouraged.…”
Section: Psychological Interventionsmentioning
confidence: 99%
“…Lo segundo, se encuentra relacionado con la percepción de ellas mismas con baja capacidad para afrontar la enfermedad y sus síntomas. Lo anterior aumenta el pesimismo, hipervigilancia del dolor, miedo y desesperanza, que no solo influyen en la percepción de dolor sino también afectan la respuesta al tratamiento (23).…”
Section: Respuesta Emocional Y Desordenes Psiquiátricosunclassified